Seroprevalence of Helicobacter pylori associated with gastrointestinal implication in pet dogs of Urmia, Iran - Sina Modainema; Mojtaba Hadian; Bahram Dalir-Naghadeh (Journal of Zoonotic Diseases, 2022)
Helicobacter pylori (H. pylori) is a Gram-negative microaerophilic, curved to spiral-shaped, motile bacterium capable of infecting humans and several animal species. The aim of this study was to quantify immunoglobulin G (IgG) antibodies to H. pylori among pet dogs in relation to gastrointestinal disturbances in Urmia (west Azerbaijan, Iran). Blood samples of 87 pet dogs (64 males and 23 females) were collected via their cephalic vein. Antibodies (IgG) against canine H. pylori were detected by a commercial enzyme-linked immunoassay assay (ELISA) utilizing a monoclonal anti-Hp-IgG antibody and Hp-IgGHRP conjugate. The results showed that 59 male dogs out of 64 and all 23 female dogs had an IgG levels greater than 100 ng/mL (94.2%). The mean (± SD) was 131 ± 10.69 ng/mL. The rest of the dogs (5 male dogs) showed IgG values below 60 ng/mL (6.8%). The mean (± SD) was 52 ± 8.52 ng/mL. Sifting through the medical backgrounds and data of the dogs showed that 63 out of 82 dogs (76.8%) with high IgG values, had a current or past history of gastrointestinal problems. The statistical analysis showed no significant difference in the prevalence of seropositive cases within different sexes and age groups (p > 0.05). The current study is the first to address the quantification of IgG titers for H. pylori in dogs in the region, showing its possible strong connection with gastrointestinal disturbances, which could thus be considered a step forward in deciphering rather complex epidemiology of H. pylori.